KEPEMIMPINAN DALAM KONTEKS PENDIDIKAN ISLAM - Maria Ulfa, Hanina (As-Sulthan Journal of Education, 2025)
Effective leadership in Islamic education poses a challenge in the era of globalization, where leaders are required to adapt to changes and engage all stakeholders. This study aims to explore the influence of inclusive and visionary leadership styles on character development and the quality of education in Islamic educational institutions. The methodology employed is a mixed-methods approach, combining qualitative and quantitative analyses to gain comprehensive insights into leadership dynamics. The findings indicate that student involvement in decision-making and the leader's role as a moral exemplar significantly contribute to a positive and productive learning environment. The implications of these findings emphasize the importance of developing more inclusive and adaptive leadership strategies, providing practical guidance for education leaders to enhance the quality of education and character development among students. This research also opens opportunities for further studies on the influence of technology and local contexts in Islamic educational leadership.